Computation of the scattering from inhomogeneous objects with a discrete rotational symmetry and a nonsymmetric part. - Soudais, P.
Using a specific solver for circulant matrices can reduce the cost of computing the scattering from a discrete rotational symmetric object by up to several orders of magnitude. A solver is developed for symmetric objects with a nonsymmetrical part (such as an antenna on a body of revolution). This solver has been implemented in a finite-element code based upon a hybrid formulation. The hybrid formulation combines integral equations and partial differential equations; it can handle inhomogeneous anisotropic objects of arbitrary shape. Results on inhomogeneous objects with defects are shown. The solver can also be used to perform a parametric study of the defects
Keywords: EM scattering; Anisotropic dielectric structures; Anisotropic objects; Circulant matrices; Conducting structures; Discrete rotational symmetry; Electromagnetic scattering; Finite-element code; Inhomogeneous objects; Integral equations; Nonsymmetrical part; Parametric study; Partial differential equations; Wire antennas